2020
DOI: 10.1177/1350650119899547
|View full text |Cite
|
Sign up to set email alerts
|

Comparative investigation of ultrasonic cavitation erosion for three materials in deionized water

Abstract: To investigate the response of material to cavitation erosion, a comparative work was carried out on three materials, aluminum, copper alloy and titanium. Ultrasonic cavitation erosion was produced as the specimen was submerged in the deionized water. Within a cavitation erosion period of 120 min, the cumulative mass loss was measured at certain time intervals. Surface structure and cavitation damage patterns were observed for the three materials. Microhardness was measured and compared. The results indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Additionally, TA31 Ti alloy exhibited a hexagonal close-packed structure with a low-slip system, which did not easily dissipate CE energy through plastic deformation under CE stress. Consequently, stress concentrations occurred at grain boundaries and defects, leading to material shedding [10] . Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, TA31 Ti alloy exhibited a hexagonal close-packed structure with a low-slip system, which did not easily dissipate CE energy through plastic deformation under CE stress. Consequently, stress concentrations occurred at grain boundaries and defects, leading to material shedding [10] . Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al reported that a sample in an oxygen-saturated solution exhibited better CE resistance than that in a nitrogen-saturated solution for the same CE time because of structural differences of the passive film in different solutions [9] . Opare et al noted that the weak slip effect of the closely packed hexagonal structure of Ti alloys protected the sample surface against CE, leading to higher CE resistance compared with Al and Cu alloys [10] . Furthermore, in NaCl solution, the CE process of Ti alloys is affected by the synergistic effect of mechanical impact damage and corrosion, causing additional material damage.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have shown that cavitation erosion of microparticles is affected by many factors such as particle size, particle concentration and substrate material (Opare, 2019; Zhang, 2017; Chen et al , 2009). The effect of different sediment particle sizes on cavitation erosion behavior of turbine blades was studied, and they found that small particle size referred to the failure mode of shock wave, and large particle size induced the failure mode of microjet (Liao et al , 2012).…”
Section: Introductionmentioning
confidence: 99%